SISTEM INFORMASI PENGENALAN TOKOH PAHLAWAN BERBASIS WEB APLIKASI MOBILE (Information Technology and Telematics, 2014)
Abstract – Along with the development of technology, smartphones are not only useful to make a call or send sms only. Smartphones have advantages over regular phone like having Multimedia function, games, applications and more others. Therefore the use of the growing number of smartphones and the growing area of utilization is expected to be helpful in providing information about Indonesian hero figures so that the Indonesian people know and appreciate the heroes who have fought for the independence of Indonesia, also increases a sense of nationalism the nation Indonesia. The purpose of the design of this system is to help introduce a national hero figures, revolution and provide information the national big day through sophistication of android smartphone which is now owned by more people. The development of applications is using the method of prototypes with mobile library jquery while software used is Eclipse with Phonegap plugins and Enterprise Architect. This application will give information details indonesian hero and a big day of the indonesian national. Keyword: Android, Hero, Prototype, Jquery mobile, phonegap